Optimization of Extraction Method and Characterization of Phycocyanin Pigment from Spirulina platensis - Elin Julianti; Susanti Susanti; Marlia Singgih; Laida Neti Mulyani (Institute for Research and Community Services (LPPM) ITB, 2019)
Spirulina platensis is a microalgae species that contains phycocyanin, a blue pigment that is widely used in the food, cosmetic and pharmaceutical industries. The objective of this study was to isolate phycocyanin from dried biomass of Spirulina platensis. The optimum extraction was through freeze-thawing extraction with 0.01 M phosphate buffer pH 7. Purification was done using 50% ammonium sulphate precipitation, dialysis, and gel filtration chromatography. The purity ratio of the purified product was 1.729 (A615/A280). Characterization of isolate, carried out using SDS-PAGE, gave molecular weights of around 15-16 Kda and using infrared spectrophotometry the similarity with the standard phycocyanin spectrum was obtained. Both methods confirmed that the isolate was phycocyanin.